Long-Lived Immunity in SARS-CoV-2-Recovered Children and Its Neutralizing Capacity Against Omicron - Sieber, Justyna; Mayer, Margareta; Schmidthaler, Klara; Kopanja, Sonja; Camp, Jeremy V.; Popovitsch, Amelie; Dwivedi, Varsha; Hoz, Jakub; Schoof, Anja; Weseslindtner, Lukas; Szépfalusi, Zsolt; Stiasny, Karin; et al. (Frontiers in Immunology, 2022)
SARS-CoV-2 infection is effectively controlled by humoral and cellular immune responses. However, the durability of immunity in children as well as the ability to neutralize variants of concern are unclear. Here, we assessed T cell and antibody responses in a longitudinal cohort of children after asymptomatic or mild COVID-19 over a 12-month period. Antigen-specific CD4 T cells remained stable over time, while CD8 T cells declined. SARS-CoV-2 infection induced long-lived neutralizing antibodies against ancestral SARS-CoV-2 (D614G isolate), but with poor cross-neutralization of omicron. Importantly, recall responses to vaccination in children with pre-existing immunity yielded neutralizing antibody activities against D614G and omicron BA.1 and BA.2 variants that were 3.9-fold, 9.9-fold, and 14-fold higher than primary vaccine responses in seronegative children. Together, our findings demonstrate that SARS-CoV-2 infection in children induces robust memory T cells and antibodies that persist for more than 12 months, but lack neutralizing activity against omicron. Vaccination of pre-immune children, however, substantially improves the omicron-neutralizing capacity.